Kombinasi Senam Mata Dan Pemberian Terapi Komplementer Herbal Kencur Terhadap Astenopia Pada Mahasiswa Keperawatan - Aryani, Atik; Widiyono, Widiyono; Ariastuti, Reni (JURNAL WACANA KESEHATAN, 2024)
Using a computer for a long duration of time can cause symptoms of Computer Eyes Syndrome or often called asthenopia. Eye fatigue is bad for health, decreasing the quality of visual acuity, decreasing one's quality of life and decreasing productivity levels. One of the efforts to overcome asthenopia with eye exercises is the Bates method and combined with the administration of kencur. This study aims to analyze the effect of Bates method eye exercises combined with kencur administration in reducing asthenopia symptoms in college students. This study used a one group pre-test post-test design. This study provides an intervention of Bates method eye exercises combined with the administration of kencur by looking at differences in asthenopia symptoms. Sampling using purposive sampling technique with a total sample size of 37 students. Asthenopia was measured using an asthenopia (eye fatigue) checklist questionnaire.Â  The results showed that before being given the intervention all respondents experienced asthenopia, then after being given the intervention for 6 days there was a decrease in asthenopia symptoms, namely 31 respondents (83.8%) did not experience asthenopia and 6 respondents (16.2%) still experienced asthenopia. The results of the difference test obtained a p value of 0.0001 (p value <0.05) which means that there is an effect of a combination of eye exercises and complementary therapy of kencur herbs on asthenopia in students of Sahid University Surakarta.